The Effect Of Transformational Leadership Style On Employee Job Satisfaction And Motivation As Mediating Variables - Sainaro, Sahdid; Haji, Son; Masrifah, Ifah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of transformational leadership style on employee job satisfaction and work motivation, as well as the mediating role of job satisfaction in this relationship at PT. Sele Raya Merangin Dua. The research questions cover four main aspects, namely: the influence of transformational leadership style on job satisfaction, the influence of transformational leadership style on work motivation, the influence of job satisfaction on work motivation, and the mediating role of job satisfaction. This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) data analysis technique using SmartPLS software. The results show that transformational leadership style has a significant effect on job satisfaction (O=0.173; T=2.046; P=0.041) and work motivation (O=0.510; T=6.678; P=0.000). Furthermore, work motivation has a significant effect on job satisfaction (O=0.625; T=8.978; P=0.000). In addition, job satisfaction is proven to significantly mediate the effect of transformational leadership style on work motivation (O=-0.146; T=2.387; P=0.017). These findings contribute theoretically to the context of human resource management in the mining sector, demonstrating the importance of transformational leadership and job satisfaction in building employee motivation.